Effectiveness of "Rasaku" Mood-Monitoring App to Prevent Depression Tendency among College Students - Ardelia, Vania; Lestari, Endang; Agindaris, Amjodti Laily; Fauzan, Rayyan Nur (International Conference on Sustainable Health Promotion, 2023)
Depression is known as a common and severe mental disorder due to its high prevalence in the world, especially among emerging adult college students. This possibly due to the transitional period which emerging adult students experienced in academic, social, or economic aspects. Inability to overcome this developmental period could potentially cause depression symptoms. Additionally, the stigmatization of mental disorders also exacerbates emerging adult students’ intention to seek help. Therefore, technology with its rapid development were expected to contribute in preventing depression, one of which through mood-monitoring app. This study aimed to assess effectiveness of “Rasaku” mood-monitoring app to prevent depression tendency among college students. A quasi-experimental study with two-group pre-test post-test conducted with 51 participants assigned in the experimental and control groups for 1-week period. Participants were college students with age between 18-25. Data were analyzed using paired sample t-tests. Results showed no significant differences in the usage of mood-monitoring app in the experimental group. Thus, “Rasaku” app might be less effective in preventing depression symptoms among emerging adult college students. Albeit it is important to note that this was a pilot study to test the app effectiveness, therefore current results could be used as reference for future studies.